Potential for cure and predictors of long-term survival after radiofrequency ablation for colorectal liver metastases: A 20-years single-center experience. Issue 12 (December 2022) - Weilert, Hauke; Sadeghi, Darja; Lipp, Michael; Oldhafer, Karl Jürgen; Donati, Marcello; Stang, Axel
Abstract: Background: Additional radiofrequency ablation (RFA) of liver-limited colorectal liver metastases (CRLM) improves overall (OS) and recurrence-free survival (RFS) over systemic therapy alone. We aimed to assess the potential and predictive factors of long-term survival and cure to optimize patient selection for RFA application. Methods: Retrospective review of a prospectively maintained single-center database of consecutive patients undergoing RFA for liver-limited CRLM after systemic therapy between 2002 and 2020. Clinicopathologic characteristics and KRAS/BRAF- genotype data (tested routinely since 2010) were correlated to RFS and OS. Cure was defined as ≥10-years RFS (long-term survival as ≥5-years OS) following RFA. Results: For the entire cohort of 158 patients (median follow-up 13.6 years), co-occurrence of three factors, RECIST-defined response, number of ≤3 CRLM, and ≤3 cm maximum size determined a survival plateau that distinguished cured from non-cured patients (10-years RFS: 15.5% vs 0%, p < 0.0001). Among 59 patients (37.3%) being tested, 4(6.8%) were BRAF -mt, 15(25.4%) KRAS -mt, and 40(67.8%) KRAS/BRAF -wt. OS (median follow-up 8.3 years) was estimated to be higher with KRAS/BRAF -wt compared to a mutant KRAS or BRAF status (5-years OS: 22.8% vs 3.4%, p = 0.0018). Conclusion: This study indicates about 15% chance of cure following RFA of low-volume liver-limited CRLM after downsizing by systemic therapy and a negative effect of KRAS or BRAF mutation on long-term survival after CRLM ablation. These findings may improve clinical decision-making in patients potentially candidate to RFA of CRLM and encourage further investigations on molecular factors determining an oligometastatic state of CRLM curable with focal ablative therapy.